Endocrine Hypertension: Overview of Current Understanding (Cardiovascular Journal, 2023)
Hypertension is a leading cardiovascular risk factor with significant morbidity and mortality. Sometimes it remains difficult to find out the actual cause and to manage in a large segment of population. So, the ability to identify a contributing or secondary cause that is potentially curable for all patient with hypertension is of great importance and challenging. Endocrine hypertension is one of the common forms of secondary hypertension. Primary aldosteronism, pheochromocytoma, and other causes of mineralocorticoid excess are among the common causes of endocrine hypertension. Published literature were reviewed about their prevalence, clinical presentation, screening methods and specific management. Now day by day it’s become more challenging for the clinicians to understand the pathophysiology, clinical spectrum of these diseases and improvement of the management protocol because of newer clinical, biochemical, and modern radiological approach.Cardiovasc j 2023; 15(2): 159-174